Masjid Az-Zikra Sentul: Transformasi dari Eco-Masjid ke Eco-Sosial: Az-Zikra Sentul Mosque: Transformation from Eco-Mosque to Eco-Social - Suwendi; Abror, Muhamad (Jurnal Bimas Islam, 2024)
Mosques are not only places of worship, but also serve as centers of education and social change. Given the increasing environmental challenges, mosques have an important role in raising ecological awareness. This study examines the implementation of eco-friendly principles at Az-Zikra Mosque in Sentul, Bogor, during the period of Khotib Kholil Foundation Chairman (2016-2022), as well as its role in educating the community about environmental conservation. Through qualitative research involving interviews, observations, and documentation, this study explores various environmentally friendly initiatives at the mosque, which include maximizing water usage, bioclimatic architectural design of mosque buildings, utilization of biogas, waste management with incineration technology, urban green space management, and plastic bottle waste alms movement. Research informants include mosque administrators, worshipers, volunteers, and the surrounding community. Using Elinor Ostrom's Theory of Co-management of Natural Resources (Commons Management), this study proves that Az-Zikra Mosque not only successfully implements ecological practices efficiently with evidence of successfully applying the concept of eco-mosque according to Green Building Council Indonesia (GBCI) standards, but is also able to make ecological activities at the mosque an effective medium of ecological education to the local community by involving them directly in environmentally conscious activities. The research findings show that mosques are able to apply a holistic approach to sustainability by optimizing natural resources, providing ecological education, and integrating environmental awareness with spiritual values. Research recommendations include increasing collaboration between mosques and communities, strengthening partnerships with government and the private sector, encouraging other mosques to adopt environmentally friendly practices, developing religious education modules that integrate ecological awareness, and creating an evaluation system to measure the impact of mosque environmental initiatives on an ongoing basis.